2010
DOI: 10.1002/ana.21827
|View full text |Cite
|
Sign up to set email alerts
|

Developmental plasticity connects visual cortex to motoneurons after stroke

Abstract: We report motor cortical function in the left occipital cortex of a subject who suffered a left middle cerebral artery stroke early in development. Transcranial magnetic stimulation of the left occipital cortex evoked contraction of right hand muscles. Electroencephalogram recorded over the left occipital cortex showed: 1) coherence with electromyogram from a right hand muscle; 2) a typical sensorimotor Mu rhythm at rest that was suppressed during contraction of right hand muscles. This is the first evidence t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 23 publications
(48 reference statements)
1
26
0
Order By: Relevance
“…Nadhim Bayatti and colleagues have demonstrated how patterns of gene expression that may represent protomaps in the human neocortex show similarities with animal models but also important differences (Bayatti et al 2008b;Ip et al 2010 in this issue), which need to be understood, considering the more complex pattern of arealization observed in humans, and the large plasticity in arealization sometimes observed following a lesion early in human brain development (Basu et al 2010). Fruitful studies have been made on the development of those regions of the cortex that show the greatest differences with other species in the mature human brain, namely the frontal ⁄ prefrontal cortex, perisylvian cortex and in particular Broca's area, the site of speech generation (Abrahams et al 2007;Judaš & Cepanec, 2007).…”
Section: Principles Of Cortical Arealization In Humanmentioning
confidence: 99%
See 1 more Smart Citation
“…Nadhim Bayatti and colleagues have demonstrated how patterns of gene expression that may represent protomaps in the human neocortex show similarities with animal models but also important differences (Bayatti et al 2008b;Ip et al 2010 in this issue), which need to be understood, considering the more complex pattern of arealization observed in humans, and the large plasticity in arealization sometimes observed following a lesion early in human brain development (Basu et al 2010). Fruitful studies have been made on the development of those regions of the cortex that show the greatest differences with other species in the mature human brain, namely the frontal ⁄ prefrontal cortex, perisylvian cortex and in particular Broca's area, the site of speech generation (Abrahams et al 2007;Judaš & Cepanec, 2007).…”
Section: Principles Of Cortical Arealization In Humanmentioning
confidence: 99%
“…James Bourne has described how multiple cortical visual areas develop in the primate brain (Bourne & Rosa, 2006;Burman et al 2007;Bourne, 2010 in this issue) and has shown that focal lesions in the immature brain lead to reorganization of the cortex in different ways to lesions in the adult brain, an issue that has been addressed in various model systems (Huffman et al 1999). Similarly, Janet Eyre and colleagues and Martin Staudt and colleagues have used a battery of techniques, including MRI and neurophysiological recordings in human subjects, to investigate different types of reorganization of the sensorimotor cortex and corticospinal tract in response to developmental lesions as compared with the effects of lesions in the adult (Basu et al 2010;Eyre et al 2007;Walther et al 2009;Staudt, 2010 in this issue). Martin Staudt and colleagues showed that when a lesion prevents formation of a direct pathway from the origin to the appropriate target the axonal tracts extend around the lesion and nevertheless reach appropriate targets, directly supporting the principle of the protomap hypothesis (Rakic, 1988) in the human brain.…”
Section: The Impact Of Imaging Techniques In Mapping Human Brain Devementioning
confidence: 99%
“…Perinatal stroke perturbs the outcome of this process to a variable extent: the best functional outcome is seen in patients who retain a crossed corticospinal tract contribution from the affected hemisphere [34]. In contrast, in patients with a poor motor outcome there is a gradual loss of crossed projections from the affected hemisphere with abnormal retention of uncrossed projections from the unaffected hemisphere [37, 38]. Animal models produce similar results and confirm the activity-dependent nature of the process [39].…”
Section: Introductionmentioning
confidence: 99%
“…Later extrinsic influences such as incoming thalamocortical afferents refine the areas of gene expression and promote the formation of cytoarchitectural differences, resulting in the final map. In humans, damage to the neocortex can occur during the pre-or perinatal period [the motor cortex and corticospinal tract are most commonly affected (Eyre, 2007)], but the developing human brain is plastic in nature, and substantial reorganization of connectivity can take place (Basu et al 2010). Studies both on human regional identity and on characterizing differentiation and origin of neurones in different regions are necessary to understand the mechanisms underlying these reorganizations.…”
Section: Introductionmentioning
confidence: 99%